Production, characterization, and immobilization of protease from the yeast Rhodotorula oryzicola - Oliveira, Juliana Mota de (2021)
The protease was produced extracellularly in submerged fermentation by the yeast Rhodotorula oryzicola using different sources of nitrogen and maximum activity (6.54 × 10−3 U/mg) was obtained in medium containing 2% casein (w/v). Purification of the protease by gel filtration chromatography resulted in a 3.07-fold increase of specific protease activity. The optimal pH and temperature for enzyme activity were 6.51 and 63.04 °C, respectively. Incubation in the presence of some salts enhanced enzyme activity, which peaked under 0.01 M BaCl2. The enzyme retained about 90% of enzymatic activity at temperatures 50–60 °C. The commercially available enzyme carriers evaluated, silica gel, Celite 545, and chitosan effectively immobilized the protease. The enzyme immobilized in Celite 545 retained 73.53% of the initial activity after 15 reuse cycles. These results are quite promising for large-scale production and immobilization of protease from R. oryzicola, as the high operational stability of the immobilized enzyme lowers production costs in biotechnological applications that require high enzymatic activity and stability under high temperatures.